Effect of gestational weight gain on pregnancy outcome of Indian mothers - Patel, Keyur; Chaudhary, Megha; Shah, Maitri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Gestational weight gain (GWG) and pre-pregnancy body mass index (BMI) play important roles in determining the pregnancy outcome. The weight gain recommendations by the IOM are based on Western WHO BMI cut-offs, making it difficult to generalize their findings to Asian Indians. We aimed to compare GWG among healthy pregnant women across different BMI with the IOM guidelines-2009. We also aimed to evaluate associated feto-maternal outcomes with GWG among the pregnant women enrolled in the study. Methods: A retrospective cohort study conducted at department of obstetrics and gynecology, from April 2019 to November 2019. Postnatal mothers whose weight was registered at first trimester of pregnancy and at term and delivered in SSG hospital were included. According to IOM Women were divided into: Group 1 less than recommended weight gain and Group 2 recommended weight gain. Results: Significant difference was seen in the baby weight between the two groups (p value <0.05). 92.75% of babies had low birth weight in Group 1 as compared to 42.21% in Group 2. On performing univariate logistic regression, significant association was seen between GWG and low birth weight (p <0.05), no association was seen between GWG and caesarean (p value >0.05), and no association was seen between GWG and preterm deliveries (p >0.05). Conclusions: Majority of patients in the both groups had term delivery. Women gaining less than recommended weight gain during pregnancy had new born with significantly lower birth weight. There was no association of mode of deliveries and GWG.